1955
DOI: 10.1161/01.cir.12.6.963
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in the Intra-Arterial Pressure during Immersion of the Hand in Ice-Cold Water

Abstract: The response of the intra-arterial pressure to the cold immersion stimulus was studied in 42 healthy young adults, continuous direct (arterial-pressure) recording being used. The average systolic elevation was 22.6 mm. Hg and the average diastolic elevation was 16.3 mm. Hg. The difference between direct and indirect methods of measuring blood pressure was studied in 351 simultaneous determinations in 35 of these young adults. The direct systolic pressure averaged 9.7 mm. Hg higher and the diastolic pressure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…It is important to stress that, if a 12-cm cuff is used for obese subjects, over estimation of arm blood pressure (cuff hypertension) may occur. 5 Our study shows a similar average difference and interindividual scatter in the hypertensive group, with a normal dimension of the upper arm, compared with the data for the obese group where a wider cuff was used. We therefore recommend a 15-cm cuff for obese subjects with an arm circumference exceeding 35 cm.…”
Section: Discussionsupporting
confidence: 76%
“…It is important to stress that, if a 12-cm cuff is used for obese subjects, over estimation of arm blood pressure (cuff hypertension) may occur. 5 Our study shows a similar average difference and interindividual scatter in the hypertensive group, with a normal dimension of the upper arm, compared with the data for the obese group where a wider cuff was used. We therefore recommend a 15-cm cuff for obese subjects with an arm circumference exceeding 35 cm.…”
Section: Discussionsupporting
confidence: 76%
“…demonstrated that the different never fibers for this response are the pain fibers, which are stimulated by placing the hand in cold water and these are the sympathetic fibers. 23 The response of 15mmHg increase in blood pressure is considered as normal response to cold pressor test in normal individuals. Gherghel et al performed a modified cold pressor response test in 24 patients with POAG and 22 controls and found a differing blood pressure and ocular blood flow response in patients with POAG suggestive of systemic autonomic failure and ocular vascular dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure and heart rate responses to sustained handgrip for 3 min at 30% of maximum voluntary con traction (measured in newtons) were measured [18]. During the cold pressor test one hand was immersed up to the wrist in ice water slush for 3 min, and heart rate and blood pressure response measured [19,20].…”
Section: Methodsmentioning
confidence: 99%